Optimization of Hub Location for Tank Car Spare Parts Distribution In East Nusa Tenggara : A Case Study of PT Elnusa Petrofin - Layman, Pauline Nancy Deslin; Sukarno, Iwan (Jurnal Logistik Indonesia, 2025)
PT Elnusa Petrofin (EPN) is a company engaged in the logistics and distribution of fuel oil (BBM) in Indonesia, including supporting the Public Service Obligation (PSO) and One Price BBM programs managed by Pertamina. The reliability of the tank car fleet is a crucial factor in this service, so PT Elnusa Petrofin implements three maintenance programs that include preventive, corrective, and overhaul maintenance. However, in five Fuel Terminals in East Nusa Tenggara, the implementation of this program is constrained by limited spare parts due to the absence of authorized dealers and the lengthy procurement process, which results in a 4% delay in tank car repairs. Therefore, this study proposes the construction of spare parts hubs or warehouses in these five locations, intending to reduce transportation costs and time and reduce repair delays. The method used is Green Field Analysis (GFA) with AnyLogistix software and Center of Gravity (CoG) to determine the optimal location of the warehouse. The GFA results show coordinates (-8.8527219759, 121.6625537826) in Tetandara, Ende Regency, while CoG produces coordinates (-8.59346303874142, 121.010483387574) in Denatana, Ngada Regency. The cost analysis shows that shipping under existing conditions, i.e. directly from Jakarta to five locations in NTT, costs IDR 44,475,500, while through a hub in Ende Regency can save up to 57.80% at a cost of IDR 18,766,000. Meanwhile, the alternative hub in Ngada Regency offers 20.20% savings at a cost of IDR 35,491,000.